A review of recent evidence in human studies of n-3 and n-6 PUFA intake on cardiovascular disease, cancer, and depressive disorders: does the ratio really matter?. (18th August 2015) - Marventano, Stefano; Kolacz, Paulina; Castellano, Sabrina; Galvano, Fabio; Buscemi, Silvio; Mistretta, Antonio; Grosso, Giuseppe
Abstract: Polyunsaturated fatty acids (PUFAs) have been considered of great interest for human health due to their potential anti-inflammatory action that may protect from a number of chronic-degenerative diseases with an inflammatory pathogenesis. This review aimed to report the most updated evidence of both n-3 and n-6 PUFAs effect on cardiovascular disease, cancer, and depression in humans. Attention has been also paid to those studies exploring the effects of the ratio intake. Results from pooled analyses of human studies reported a general positive effect of n-3 PUFAs intake on all outcomes considered. In contrast, the role of n-6 PUFAs on human health needs to be better assessed in order to clearly identify which compound exerts beneficial/harmful effects. Only a limited number of clinical studies considered the n-3:n-6 PUFAs ratio, rather reporting contrasting results. A number of limitations when considering the ratio between these two families of PUFAs have risen.